The Evaporation on the Tibetan Plateau Stops Increasing in the Recent Two Decades. Issue 23 (9th December 2022) - Wang, Liming; Han, Songjun; Tian, Fuqiang; Li, Kunbiao; Li, Yukun; Tudaji, Mahmut; Cao, Xuejian; Nan, Yi; Cui, Tong; Zheng, Xinyuan; Hu, Zhaoyong; Wang, Weiguang; et al.
Abstract: As a crucial variable in hydrological and climate modeling, a lot of efforts have been made to estimate the evaporation ( E, including soil evaporation, canopy interception, and plant transpiration) on the Tibetan Plateau (TP). Most studies showed that the evaporation on the TP stops increasing or even decreases in the recent two decades. However, the spatio‐temporal variability of this phenomenon and its underlying mechanism remains uncertain. Here, we utilized a state‐of‐the‐art version of the sigmoid generalized complementary equation to estimate the monthly evaporation over the TP for the period of 1979–2018. The results show that the annual E increases significantly during 1979–1998 with a rate of 1.94 mm yr −1 (based on the total E over the TP), however, it decreases during 1999–2018 with a rate of −1.06 mm yr −1 . The most significant decreasing trend of E occurs in the spring. The areas with the most significant decrement of E include the central and western Qiangtang Plateau, the middle reaches of Yarlung Zangbo River, and the Yangtze River basin. By introducing a new aridity index R we, we identified that the decrement of E mainly occurs in the water‐limited regions, which contribute to 60% of the total decreasing trend of the whole region; at the same time, the energy‐limited regions also contribute to 40% of the decreasing trend. This study is important for the hydrological researches and decision making because the trend of E can influence the water resources and agriculture. Plain Language Summary: Terrestrial ( E ) connects the water cycle and energy flow in the earth‐atmospheric system. A lot of studies have tried to estimate E on the Tibetan Plateau (TP). Most studies showed that the evaporation on the TP decreased in the recent two decades, but its underlying mechanism is not clear. In this study, we estimated the monthly evaporation over the TP using the sigmoid generalized complementary equation. We found that the annual E increases during 1979–1998, however, it decreases during 1999–2018. The decrement of E mainly occurs in the water‐limited regions (60%), but also in the energy‐limited regions (40%). The seasonal variation and spatial variation of E were further studied to explain the decrement of E in the recent two decades. Key Points: The high accuracy of the estimated E was validated at the site scale and basin scale The mean annual E increases during 1979–1998, however, decreases during 1999–2018 The water‐limited regions contribute 60% to the decrement of E during 1999–2018